The Neurobiology of Decision-Making and Responsibility: Reconciling Mechanism and Mindedness - Shadlen, Michael N.; Roskies, Adina L. (Frontiers in Neuroscience, 2012)
This essay reviews recent developments in neurobiology which are beginning to expose the mechanisms that underlie some elements of decision-making that bear on attributions of responsibility. These “elements” have been mainly studied in simple perceptual decision tasks, which are performed similarly by humans and nonhuman primates. Here we consider the role of neural noise, and suggest that thinking about the role of noise can shift the focus of discussions of randomness in decision-making away from its role in enabling alternate possibilities and toward a potential grounding role for responsibility.